Characterisation of post-translational and transcriptional reprogramming of the immune response to ISAV and IPNV infections in salmon head kidney cells - Stewart, Robert; Guitián, Xoel Souto; Gervais, Ophélie; Jin, Yehwa; Salisbury, Sarah J.; Ballantyne, Maeve; Martin, Samuel A. M.; Orosa-Puente, Beatriz; Robledo, Diego (Frontiers in Immunology, 2025)
Viral diseases remain a major barrier to the sustainable production of farmed fish, primarily attributable to the absence of effective prevention and treatment options. Understanding host-pathogen interactions can guide the development of vaccines, antiviral therapies, or gene editing strategies. Ubiquitination is a post-translational modification capable of regulating protein activation, structure, and degradation. As such, it is known to regulate many aspects of immune functions in model species, but is currently understudied in fish. This study leverages ubiquitin-enriched mass spectroscopy complemented with RNA sequencing to characterise the role of ubiquitination in response to infection. A challenge experiment was conducted by infecting Atlantic salmon head kidney (SHK-1) cells with Infectious salmon anaemia virus (ISAV) and Infectious pancreatic necrosis virus (IPNV). At 24 and 48 hours post-infection, dramatic changes were observed in the global ubiquitination state of host proteins. Many post-translational modifying proteins increased in abundance upon ISAV infection, whilst IPNV infection resulted in a reduction in abundance of many of these proteins. Transcriptomics showed a delay in the activation of the antiviral response to ISAV infection, with major upregulation of genes associated with immune pathways only at 48h. On the contrary, IPNV infection resulted in upregulation of classic innate immune response genes at both timepoints. Clear activation of Rig-like receptor pathways is demonstrated in both infections, in addition to upregulation of both conserved and novel antiviral TRIM E3 ubiquitin ligase genes. Network analysis identified clusters of immune genes and putatively regulatory proteins showing differential ubiquitination upon viral infection. This study highlights the capacity of post-translational control of the host innate immune response to viruses in Atlantic salmon. Clear differences in ubiquitination between the two viruses indicate either virus-specific post-translational regulation or viral antagonism of the immune response. Additionally, the ubiquitination of various proteins was linked to the regulation of innate immune pathways, suggesting a direct role of ubiquitination in the regulation of antiviral responses.